Strengthening implementation of the Guiding Principles by affected states - Cotroneo, A (Refugee Studies Centre, University of Oxford, 2018)
Engaging with States affected by internal displacement by facilitating peer-to-peer exchanges on shared challenges and through tapping into the potential for mobilisation by sub-regional and regional forums can prompt national action and strengthen implementation of the Guiding Principles.